Centre for Applied Language Studies, University of Limerick, Ireland. (13th March 2015) - Chambers, Angela; Atkinson, David; Farr, Fiona
<x content-type="archive" xml:space="preserve">Abstract</x> The Centre for Applied Language Studies (CALS), founded in 1997, brings together researchers and postgraduate students from several disciplines in language studies, and is structured in three research clusters: New learning environments; Discourse, society and identity; and Plurilingualism and language policy. There is a certain amount of overlapping between the clusters, and several researchers are active in more than one cluster. Thus research in language teacher education is present both in the New learning environments cluster and in Discourse, society and identity. Corpus-based methodologies are also prominent in both these clusters. Furthermore, discourse analysis is present as a methodology in all three. The following sections provide information on current research and selected research outcomes within the three research clusters from 2011 to 2013.